THE ROLE OF CHOLESTEROL PROVISION FUNCTIONAL SYSTEM IN THE DEVELOPMENT OF ATHEROSCLEROSIS - Y. V. Abakumova; N. A. Ardamatsky (Российский кардиологический журнал)
The role of cholesterol provision functional system in the development of atherosclerosis.